Pembinaan Karakter Anak Berhadapan dengan Hukum (ABH) Melalui Page Grup di Lembaga Penyelenggaraan Kesejahteraan Sosial (LPKS) Dharmapala Indralaya - Fitriana Fitriana; Sri Safrina; Nurbuana Nurbuana; Nurhasan Nurhasan (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2023)
The character development of children who are in conflict with the law is an important process to help children understand the consequences of their actions and improve their behavior in a more positive direction. The following are some steps that can be taken in building the character of children who are in conflict with the law, including by having open communication, enforcing rules, fostering values and ethics, alternative education, the role of role models for parents to be role models and providing psychological support. It is important to remember that every child is unique, and character building methods can vary depending on each child's needs and situation. If a child is involved in a serious legal matter, it is important to seek help from a qualified professional, such as a counselor or child attorney, to provide proper guidance and support.